Photovoltaic activity in a ZnTe/PEO-chitosan blend electrolyte junction - Mohamad, S.A.; Yahya, Rosiyah; Ibrahim, Zainukl Abidin; Mohd Arof, Abdul Kariem (ELSEVIER, 2007)
A ZnTe/polymer junction has been fabricated and the photovoltaic properties studied. The polymer is a blend of 50 wt% chitosan and 50 wt% polyethylene oxide (PEO). The polymer blend was complexed with ammonium iodide (NH4I) and some iodine crystals were added to the polymer-NH4I solution to provide the I-/I3- redox couple. The ionic conductivity of the polymer electrolyte is 4.32×10-6 S cm-1 at room temperature. ZnTe was electrodeposited on ITO conducting glass. The polymer film was sandwiched between the ZnTe semiconductor and an ITO glass to form a ZnTe/polymer electrolyte/ITO photovoltaic cell. The open circuit voltage (Voc) of the fabricated cells ranges between 300 and 400 mV and the short circuit current between 2 and 5 μA.